2020
DOI: 10.1002/ca.23632
|View full text |Cite
|
Sign up to set email alerts
|

The process of curricular integration and its effects on anatomical knowledge retention

Abstract: IntroductionIntegration has been recognized as an important aspect of medical education. After transitioning from a discipline‐specific to a systems‐based preclinical curriculum, we examined faculty perceptions of the integrated approach and also whether it would lead to better anatomy knowledge retention.MethodsTo understand faculty perspectives, we reviewed curricular materials, interviewed block directors, and observed educational sessions. We analyzed knowledge retention through a 27‐question anatomy test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…The study found that the time constraints and the pre-defined learning objectives were felt as being responsible for this. The reduction in content of pre-clinical disciplines as a consequence integrated curriculum has been documented in a study by Xian Zhao et al (Zhao et al, 2020) Our findings are supported by the assertions made by researchers in another study where they stated that since the integrated curriculum focuses on the breadth of knowledge, in the process the depth of knowledge may be compromised. (Ramachandra & Muttalib, 2020) According to Edward Finnerty over the last two decades a complete elimination of the laboratory exercise in basic sciences disciplines being taught in medical colleges has taken place.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The study found that the time constraints and the pre-defined learning objectives were felt as being responsible for this. The reduction in content of pre-clinical disciplines as a consequence integrated curriculum has been documented in a study by Xian Zhao et al (Zhao et al, 2020) Our findings are supported by the assertions made by researchers in another study where they stated that since the integrated curriculum focuses on the breadth of knowledge, in the process the depth of knowledge may be compromised. (Ramachandra & Muttalib, 2020) According to Edward Finnerty over the last two decades a complete elimination of the laboratory exercise in basic sciences disciplines being taught in medical colleges has taken place.…”
Section: Discussionsupporting
confidence: 86%
“…(Azzalis et al, 2012) A study conducted to test the retention of anatomy content taught through integrated approach also reported an improvement in retention for the content taught through the integrated curriculum. (Zhao et al, 2020) The integrated curriculum promotes a strong understanding and retention of knowledge as reported by Sarah Fraser et al and this is in agreement with the findings of our study. (Fraser, Wright, van Donkelaar, & Smirl, 2019) The study finding also parallels the assertions made that breaking down the boundaries between basic and clinical sciences would improve retentions.…”
Section: Students Perception Of the Importance Of Disciplinesupporting
confidence: 93%
“…With the development of medical education, the integration of basic and clinical knowledge has become a trend in medical education reform [13] . It is believed that medical students should be taught clinical knowledge and cultivate medical capacity as early as possible [14] . In this study, we combined the basic knowledge of anatomy with clinical endoscopic surgery, encouraged students to discover, analyze and solve the problems encountered in the classes, and then summarized and deepened the related knowledge.…”
Section: Discussionmentioning
confidence: 99%